Analysis of Total Quality Management on Competitive Performance of Oil and Gas Industry - Seto Sulaksono Adi Wibowo; Febri Yogarina Adisty (Pusat P2M Politeknik Negeri Batam, 2017)
The article examines the total quality management in oil and gas industries to prove its effect on the competitive performance. The data that used in this research is secondary data by using a questionnaire that was distributed to several oil and gas industry companies. Test result which using classic assumption showed that the questionnaire considered normal does not happen multicollinearity and heteroscedasticity. The data was tested using multiple linear regressions. The data is tested simultaneously and partially. The result of total quality management is proven to have a significant relationship to competitive performance. But partially not all components of total quality management had proven to affect competitive performance. This is because the test only using multiple linear regressions so that the results obtained are less specific.